2015
DOI: 10.5325/transportationj.54.3.0368
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies for Overcoming Constrained Supply Chain Technology: An Exploratory Study

Abstract: Conditions experienced in developing countries are characterized by high levels of uncertainty and differ considerably from those encountered in developed countries. Specifically, operational environments in developing countries constrain the supply chain technology (SCT) used by firms to manage supply chain operations. Hence, it is reasonable to conjecture that firm's operating in these types of environments might rely on and use SCT and the information they provide to manage their supply chain operations dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…), integrative and organic discursive styles (Dirsmith and Haskins ), and information sharing (Saldanha et al . ). Further, within organic structures, social networks exceeded the prescribed interaction patterns; in mechanistic structures, social networks adhered to prescribed patterns (Tichy et al .…”
Section: Learning and Communicationmentioning
confidence: 97%
See 1 more Smart Citation
“…), integrative and organic discursive styles (Dirsmith and Haskins ), and information sharing (Saldanha et al . ). Further, within organic structures, social networks exceeded the prescribed interaction patterns; in mechanistic structures, social networks adhered to prescribed patterns (Tichy et al .…”
Section: Learning and Communicationmentioning
confidence: 97%
“…The results of research examining the impact of structure on communication among employees both within and across organizational boundaries indicated that organic structures, compared with mechanistic structures, were associated with more open communication styles, including communication concerning broader issues (Young 1978), consultative communication styles (Courtright et al 1989), integrative and organic discursive styles (Dirsmith and Haskins 2007), and information sharing (Saldanha et al 2015). Further, within organic structures, social networks exceeded the prescribed interaction patterns; in mechanistic structures, social networks adhered to prescribed patterns (Tichy et al 1979).…”
Section: Internal and External Communicationmentioning
confidence: 99%
“…There are 10 strategies to improve and overcome supply chain constraints according to Simatupang et al (2004) namely utilizing an ERP system that has automatic features and supply chain management functionality, using standardization of ERP, increasing supply chain transparency, gaining data insights through ERP, real-time inventory management, monitoring vendor performance, level of awareness of expenses, increasing return management, just-in-time model and streamlined accounting. However, with the conceptual integration of the previous theory and the conceptual framework of the theory above (Simatupang, et al, 2004) (Saldanha, et al, 2015) (Simatupang, et al, 2004) (Larsen & Bagchi, 2002) (Sanders & Premus, 2005), this paper has identified four main strategies that will be used in analyzing overcoming supply chain constraints in Indonesia. The four main strategies are based on increasing supply chain transparency, real-time inventory management, monitoring vendor work, and level of awareness of expenses.…”
Section: Literature Summarymentioning
confidence: 99%
“…The supply chain can also be influenced by organizational constraints because it has a significant role in the organizational development process. For instance, Saldanha et al [52] indicated that operational environments can constrain supply chain technology based on the investigations of 46 logistics and supply chain managers in India. Song and Wang [53] showed that capital constraints can reduce the profits of downstream manufacturers and even the whole supply chain, which is harmful for the sustainable development of the supply chain.…”
Section: Research Status Of Organizational Constraintsmentioning
confidence: 99%
“…In addition, the organizational structure can constrain the production of culture [76], product constraints can influence research and development team creativity [94], and the reduction of organizational slack can facilitate the migration of organizational boundary activities from the organization to the work unit level [95]. An exploratory method was also used to study the relationship between operational environments and supply chain technology [52].…”
Section: Research Status Of Organizational Constraintsmentioning
confidence: 99%